The effect of tourism investment on the distribution of income sources in Iraq for the years (2000-2015) - al kabi, Auday sabeeh lazim (International Journal of Psychosocial Rehabilitation, 2020)
Iraq possesses a varied and rich tourism wealth, with biological and climatic diversity, which constitutes an attraction for recreational tourism and the presence of many sacred thresholds that formed a magnet for religious tourism, but due to Iraq’s conditions of war and its exposure to international terrorism, the government has limited the tendency of the government to take care of this sector as it relied only on Oil revenue, but despite everything, religious tourism remained active and positive impact within tourism revenue and non-oil GDP using the kayak model. The study concluded that there is a direct relationship between tourism revenue and GDP, and this requires Among us is to give a prominent role and great importance to the tourism industry in increasing income by providing tourism services such as transportation and hotel services, and the participation of the private sector in them, as well as linking Iraq with all Islamic countries by modern means .